2022
DOI: 10.26655/jmchemsci.2022.4.13
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study aims to present the evolvement and characterization of two innovative bioactive coating composite materials overlying Yttria-stabilized tetragonal zirconia substrate. The differential analyses between artificial CaCO3/SiO2 and novel natural prepared CaCO3/SiO2 composite implantcoating material. The methodology of the present study involved forty disc-shaped specimens with a dimension of 10 mm, and twenty disc-shaped samples with 50 mm diameter were prepared from partially sintered Yttria-stabilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Many medicinal plants, either raw or processed or in fruits and teas, can be used for therapeutic purposes and have therapeutic applications [74][75][76][77][78][79]. Studies demonstrated that edible herbs can be used for human health due to their active ingredients and medicinal and antioxidant compounds [78][79][80][81][82][83].…”
Section: Toxicological Studiesmentioning
confidence: 99%
“…Many medicinal plants, either raw or processed or in fruits and teas, can be used for therapeutic purposes and have therapeutic applications [74][75][76][77][78][79]. Studies demonstrated that edible herbs can be used for human health due to their active ingredients and medicinal and antioxidant compounds [78][79][80][81][82][83].…”
Section: Toxicological Studiesmentioning
confidence: 99%
“…Nowadays, along with the growing demand of mankind for new nanotechnologies, chemical nanotechnologies are also developing rapidly. Therefore, in the field of nanochemistry, the scientific literature pays great attention to the development of nanotechnologies and their application is of high significance in various fields of human activity, by "nanoscience", we mean the branch of science concerned with the characterization and study of nanomaterials in addition to determine their physical and chemical properties between (1-100 nanometers) [12]. The goal of this study was to see how different biological silica concentrations derived from rice husk affected a few mechanical properties of a high impact strength heat cure acrylic denture base.…”
Section: Introductionmentioning
confidence: 99%